Implikasi Hak Anak Dalam Kandungan Terhadap Kebijakan Kesehatan Ibu Dan Anak - Bagas Armayoga; A. Ikhlas Muhtar Hadi; Erlina Erlina; Umi Hijriyah (Journal on Education, 2024)
Health is a state of physical, mental and social well-being that enables every person to live a socially and economically productive life. MCH events can occur starting from when the fetus is still in the womb and only become visible when the child is two years old. The aim of this research is to determine the implications of the rights of unborn children on maternal and child health policies. The research method used in this research is qualitative research, then this research uses research specifications that are descriptive analysis. The research results show that the health of children in the womb has an impact on health policy, because mothers and children are a vulnerable group and need to receive priority in health efforts. The implication of the rights of unborn children for health policy is that the fetus has the right to life. Women who exercise their reproductive rights also have obligations and responsibilities to maintain the life of the fetus.